Big data adoption: does it have a great impact on crowdfunding success in SMES? - Andaru, F. Mario (2023)
Purpose – One of the problems of MSMEs is the limited capital they have to build their business. The presence of the Crowdfunding platform is a solution for MSMEs to find investors to fund their businesses. The problem is, not all investors want to fund these MSMEs and as a result, many MSMEs do not get funds from crowdfunding. The purpose of this research is to find out whether the adoption of Big Data can affect crowdfunding success. In this case, making investors does it feel more confident about investing? Design/methodology/approach – This study collects articles regarding the adoption of big data in SMEs in the Emerald Insight Database. Furthermore, we also collected articles from the research conducted by Deng et al. in 2022 regarding factors influencing crowdfunding success. Findings – We found that the adoption of big data may represent several factors that influence crowdfunding success. In other words, if MSMEs actors apply big data to their business, it is very likely that they will gain the investors´ trust and receive the funds they need. Originality/value – This research provides an overview for MSMEs actors to consider the adoption of big data in their business. If MSMEs actors have implemented it, then apart from having a good effect on business operations, they will also find it easier to get crowdfunding success.